Study of high protein dairy powder (MPC80) susceptibility to fouling and efficacy of micro-nano-bubble aqueous ozone in removal of Bacillus spp. biofilms on stainless steel surfaces - Gandhi, Gagan (Kansas State University, 2018)
Fouling and biofilm formation on stainless-steel (SS) surfaces can be sources for cross-contamination and pose a great threat to the public health and food quality. The dairy industry needs an intervention strategy focusing on technologies discouraging the biofilm attachment and developing a sustainable eco-friendly approach for biofilm removal from the dairy processing surfaces. Since fouling encourages the attachment of bacteria to the SS surfaces, it becomes important to study the ways of reducing the fouling. The bacterial attachment to the fouled SS surfaces can be prevented by modifying the SS surface properties by chemical (using coatings) or mechanical methods. On the other hand, the degree of fouling can also be reduced by using good quality raw materials. The objective-1 of the study was focused on understanding the relationship between effect of milk protein concentrate (MPC80) solubility characteristics and fouling on SS surfaces during thermal processing. The powders were stored at different temperatures (25 °C and 40 °C) for 2 weeks to generate powders with different dissolution characteristics. Fouling characteristics of reconstituted MPC80 powder were studied using a custom-built benchtop plate heat exchanger. Exposing the MPC80 powder to a higher temperature during storage (40 °C) significantly decreased the solubility and increased the amount of foulant on SS coupons (P < 0.05). Microscopic investigations (scanning electron microscopy and laser scanning confocal microscopy) of resulting fouled layers revealed heterogeneous fouling layers of varying tomographies, consisting of lipids, proteins, and calcium. In the second study, the efficacy of Micro- and Nano-bubble aqueous ozone (MNAO) as a disinfectant was studied in removal of Bacillus cereus and Bacillus licheniformis biofilm from the SS surface. For the Bacillus cereus biofilm removal, a log reduction of only 0.68 cfu/cm² was observed after the de-ionized water wash. Whereas both MNAO and cleaning-in-place (CIP) treatments significantly reduced the bacterial counts by 2.43 and 2.88 log10 cfu/cm², respectively. On the other hand, for the Bacillus licheniformis biofilm removal from SS surfaces, a significant log reduction observed was 1.45, 3.03, 2.92 log10 cfu/cm², respectively after de-ionzed water, MNAO, and CIP treatments. Thus, it was observed that MNAO has great potential for removal of Bacillus cereus and Bacillus licheniformis biofilms from the SS surface, and can be used in the dairy industry as an effective sanitizer/disinfectant
Keywords: Fouling; Biofilm; Solubility; Ozone; Stainless steel